(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The overview of practical experiences regarding surrogacy is very various, thus implies different legal choices in order to respect the principle of equality. The multiplicity of situations should induce the Italian lawmakers to address the issue in a new perspective, as the complete prohibition is not a realistic option. Making a com-parison with other States, the essay intends to support the idea of a legal regulation regarding parentage between the child born from surrogacy and the commissioning couple in particular contexts. The logic of absolute ban should be abandoned in certain cases, precisely when the woman who wants to become mother cannot gestate the pregnancy. Exceptionally, the rigid legislative model of motherhood should be put aside, adopting a method based on the continuous reference to the fundamental principles of protection of human rights.